THE INVESTOR–STATE ARBITRATION LEGITIMACY CRISIS: COULD AI BE ITS FUTURE SAVIOR (OR RESURRECTOR)? - Dar, Wasiq; Praštalo, Boris (Pravni zapisi, 2023)
The world of arbitration has not escaped the all-pervading impact of AI. Stakeholders are not only assessing the current impact of AI on the practice of arbitration but also speculating on its future role. The possibility of AI replacing human arbitrators has also figured in the discussions. This paper focuses on the use of AI in the context of investor–State arbitration, which of late, has been facing fierce backlash for its purported deficiencies. The paper explores whether AI could be used to remedy some of the burning issues in the investor-state dispute settlement system, which have culminated in its “existential crisis”. The paper assesses the extent to which human arbitrators and other relevant factors have contributed to the crisis, and then examines the suitability of AI to act as an arbitrator. The paper lays a road map for the potential role of AI in ISA and attempts to answer the central question – could AI prove to be a resurrector or a disruptor of the ISA system.
Keywords: Artificial Intelligence; Arbitration; Decision Making; Investor-State Dispute Settlement; Investor-State Arbitration